Characteristics and Management of Autoimmune Disease-Associated Cerebral Venous Sinus Thrombosis - Zhang, Baizhuo; Lang, Yue; Zhang, Weiguanliu; Cui, Li; Deng, Fang (Frontiers in Immunology, 2021)
Cerebral venous sinus thrombosis (CVST) is a central nervous system disease characterised by thrombosis in cerebral venous or dural sinuses. Autoimmune diseases, a series of diseases caused by immune responses to autoantigens, are important causes of CVST. The most common diseases that lead to CVST are Behçet’s syndrome, systemic lupus erythematosus, antiphospholipid syndrome, and Sjögren’s syndrome. Each of these diseases have different clinical and imaging manifestations and treatment for CVST varies by aetiology. This review summarises the characteristics and the current management strategies for autoimmune disease-associated CVST and emphasises controversial therapeutic strategies to provide informative reference information for diagnosis and treatment. Risk factors of autoimmune antigens should not be neglected when unconventional CVST occurs, and both drugs and interventional therapy need further standardisation and discussion with more prospective clinical studies.